Optimal dosing time of Dachengqi decoction for protection of extrapancreatic organs in rats with experimental acute pancreatitis - Yao, Jia-Qi (World J Gastroenterol, 2020)
BACKGROUND: Acute pancreatitis (AP) is a pancreatic inflammatory disorder that is commonly complicated by extrapancreatic organ dysfunction. Dachengqi decoction (DCQD) has a potential role in protecting the extrapancreatic organs, but the optimal oral administration time remains unclear. AIM: To screen the appropriate oral administration time of DCQD for the protection of extrapancreatic organs based on the pharmacokinetics and pharmacodynamics of AP rats. METHODS: This study consisted of two parts. In the first part, 24 rats were divided into a sham-operated group and three model groups. The four groups were intragastrically administered with DCQD (10 g/kg) at 4 h, 4 h, 12 h, and 24 h postoperatively, respectively. Tail vein blood was taken at nine time points after administration, and then the rats were euthanized and the extrapancreatic organ tissues were immediately collected. Finally, the concentrations of the major DCQD components in all samples were detected. In the second part, 84 rats were divided into a sham-operated group, as well as 4 h, 12 h, and 24 h treatment groups and corresponding control groups (4 h, 12 h, and 24 h control groups). Rats in the treatment groups were intragastrically administered with DCQD (10 g/kg) at 4 h, 12 h, and 24 h postoperatively, respectively, and rats in the control groups were administered with normal saline at the same time points. Then, six rats from each group were euthanized at 4 h and 24 h after administration. Serum amylase and inflammatory mediators, and pathological scores of extrapancreatic organ tissues were evaluated. RESULTS: For part one, the pharmacokinetic parameters (C max, T max, T 1/2, and AUC 0 → t) of the major DCQD components and the tissue distribution of most DCQD components were better when administering DCQD at the later (12 h and 24 h) time points. For part two, delayed administration of DCQD resulted in lower IL-6 and amylase levels and relatively higher IL-10 levels, and pathological injury of extrapancreatic organ tissues was slightly less at 4 h after administration, while the results were similar between the treatment and corresponding control groups at 24 h after administration. CONCLUSION: Delayed administration of DCQD might reduce pancreatic exocrine secretions and ameliorate pathological injury in the extrapancreatic organs of AP rats, demonstrating that the late time is the optimal dosing time.